ANALISIS PENGARUH KEPUTUSAN PEMBELIAN PELANGGAN LUWES PURWODADI DITINJAU DARI KUALITAS PELAYANAN, LOKASI, DAN HARGA - Arma, Aulia; Rahmadi, Rahmadi; Pertiwi, Dyah Nurul Bayu; Sanjaya, Kharel Satriya (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
The current development of the business world has resulted in every human being experiencing changes in patterns of increasingly fierce behavioral competition in the business world. Every company generally wants to be successful and superior in running its business. Every business actor must be sensitive to every change and place an orientation on customer satisfaction, one of which is purchasing decisions which are influenced by several factors, namely service quality, product price, and location. For this reason, this research aims to this research is to determine the influence of purchasing decisions on customers of Luwes Purwodadi in terms of service quality, location and price. The population in this study were all customers of customers of Luwes Purwodadi. Determining the sample in this research uses Accidental Sampling, namely sampling based on chance, meaning that if the researcher meets someone then that person can be used as a research sample, if the person they meet is suitable as a data source, and the main criteria being that the person they meet is a customer or consumers of customers of Luwes Purwodadi. The data collection method uses interview techniques and questionnaires with a Likert scale. The data analysis method uses the classic assumption test, multiple regression test, and hypothesis testing. The results of this research are that the service quality variable has a significance value of 0.000 < 0.05 and a t value of 3.948 > t table 1.986. So it can be said that service quality has a positive and significant effect on purchasing decision variables. The product price variable has a significance value of 0.000 < 0.05 and a t value of 7.170 > t table 1.986. So it can be said that product price has a positive and significant effect on purchasing decision variables. The location variable has a significance value of 0.466 > 0.05 and the calculated t value is 0.732 < t table 1.986. So it can be said that location does not affect purchasing decision variables. The conclusion that can be drawn from this research is that service quality has a positive and significant effect on purchasing decisions at the customers of Luwes Purwodadi. Product prices have a positive and significant effect on purchasing decisions at the customers of Luwes Purwodadi. Location does not have a significant effect on purchasing decisions at the customers of Luwes Purwodadi. It is hoped that further research can improve this research by analyzing other factors that influence purchasing decisions at the customers of Luwes Purwodadi, such as promotions, supporting facilities, and others.